Automation of requirements: user stories generated from an objective-oriented model based on the notation i* - Lucero Guevara, Delicia Esmeralda (2018)
This paper describes the implementation of a tool for automated generation of user stories from a graphical model. The objective-oriented modeling approach is applied, which uses the notation i*. The main rationale is that the business objective is not the one that changes, but the ways in which it can be achieved. Once the requirements are compiled through this model, user stories are generated automatically for later traceability. These comply with the basic standard proposed in agile methodologies ensuring that, when arriving at the hands of the developer, there are no ambiguities in either of the two perspectives: graphical and narrative. The results of the tests with developers and analysts, as well as the application of a questionnaire, showed that the proposed tool contributes directly to the establishment of precise, complete and consistent requirements, optimizing the time used by the team members.